1983
DOI: 10.1152/jappl.1983.54.5.1306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-adrenergic blockade on ventilation and gas exchange during exercise in humans

Abstract: The effects of beta-adrenergic blockade induced by intravenous propranolol hydrochloride (0.2 mg/kg) on ventilatory and gas exchange responses to exercise were studied during tests in which the work rate was either increased progressively or maintained at a constant load in six healthy young male subjects. Heart rate during exercise decreased by about 20% and cardiac output, as estimated by a modification of the method of Kim et al. (J. Appl. Physiol. 21: 1338-1344, 1966), by about 15%. The relation between wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
1
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 0 publications
12
44
1
1
Order By: Relevance
“…Another reason for Vo, to be decreased (Twentyman et al, 1981;Petersen et al, 1983;Sue et al, 1983) may be a reduction of cardiac output which, despite an increased arterial mixed venous 02 difference (Ekblom et al, 1972;Epstein et al, 1965;Astrom, 1968) (Turner, 1983) and, particularly, on the reduction of ventilatory response to CO2 (Patrick & Pearson, 1980). Recently, Butland et al (1983) found a clear reduction of hyperventilation in exercising patients with emphysema and a good therapeutic effect in hyperventilating children has also been described (Joorabchi, 1977), after P-adrenoceptor blockade.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another reason for Vo, to be decreased (Twentyman et al, 1981;Petersen et al, 1983;Sue et al, 1983) may be a reduction of cardiac output which, despite an increased arterial mixed venous 02 difference (Ekblom et al, 1972;Epstein et al, 1965;Astrom, 1968) (Turner, 1983) and, particularly, on the reduction of ventilatory response to CO2 (Patrick & Pearson, 1980). Recently, Butland et al (1983) found a clear reduction of hyperventilation in exercising patients with emphysema and a good therapeutic effect in hyperventilating children has also been described (Joorabchi, 1977), after P-adrenoceptor blockade.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, similar studies did not always show consistent results. For instance, all studies performed on healthy subjects who were able to reach high work rates (usually more than 200 W) showed a reduction of oxygen uptake and maximum work capacity after 3-adrenoceptor blockade (Pearson et al, 1979;Anderson et al, 1979;Twentyman et al, 1981;Tesch & Kaiser, 1983;Petersen et al, 1983), whereas no changes were found in studies carried out in subjects unable to reach such work levels, either healthy (Leitch et al, 1980) or suffering from mild hypertension (Fagard et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Several studies have examined the kinetics of Vo 2 during arm and leg exercise in able-bodied subjects. 19,20,25 These studies consistently found that Vo 2 kinetics were longer for arm than for leg exercise during moderate exercise, and slowed to a greater degree during heavy exercise (as blood lactate concentrations rose) compared to leg exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A number of mechanisms have been proposed to account for these ventilatory effects of p-adrenoceptor blocking drugs which we have reviewed. It seems to us that effects on rate of cardiovascular adjustment and CO2 transport (Brown et al, 1976;Twentyman et al, 1981;Petersen et al, 1983) is the mechanism that is most likely on the present evidence to explain the effects on submaximal minute ventilation.…”
Section: Discussionmentioning
confidence: 58%
“…Enhanced hypoxic drive during exercise (Cunningham et al, 1968) may have as its basis increased sympathoadrenal activity. However, several studies have failed to demonstrate an effect on minute ventilation during graded exercise in normal subjects (Pearson, et al, 1979;Leitch et al, 1980;Petersen et al, 1983;O'Neill et al, 1984;McLeod et al, 1985) whereas others have shown reductions in minute ventilation after propranolol at submaximal levels of exercise (Twentyman et al, 1981;Violante et al, 1984).…”
Section: Introductionmentioning
confidence: 99%